2018
DOI: 10.3126/hprospect.v17i1.20351
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in low-and middle income countries (LMICs): Going beyond the need for funding

Abstract: Despite being globally recognised as an important public health issue, mental health is still less prioritised as a disease burden in many Low-and Middle-Income Countries (LMICs). More than 70% of the global mental health burden occurs in these countries. We discussed mental health issues in LMICs under themes such as abuse and mental illness, cultural influence on mental health, need for dignity in care, meeting financial and workforce gaps and the need for national health policy for the mental health sector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…In low-and-middle income countries (LMICs), service user and caregiver involvement has been widely recommended as an essential ingredient of strengthening weak mental health systems [ 14 , 15 ], which has potential to increase the likelihood of scale-up of appropriate and quality mental healthcare [ 16 , 17 ], and reduce the treatment gap for quality care [ 8 , 18 ]. However, in LMICs, there is less prioritization and government support for either mental healthcare provision or involvement of service users [ 19 , 20 ]. Furthermore, there are often no policies and laws to direct mental health programs and/or the policies and laws are not fully in line with human rights recommendations (e.g., service user participation) or are poorly implemented [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In low-and-middle income countries (LMICs), service user and caregiver involvement has been widely recommended as an essential ingredient of strengthening weak mental health systems [ 14 , 15 ], which has potential to increase the likelihood of scale-up of appropriate and quality mental healthcare [ 16 , 17 ], and reduce the treatment gap for quality care [ 8 , 18 ]. However, in LMICs, there is less prioritization and government support for either mental healthcare provision or involvement of service users [ 19 , 20 ]. Furthermore, there are often no policies and laws to direct mental health programs and/or the policies and laws are not fully in line with human rights recommendations (e.g., service user participation) or are poorly implemented [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In low-and-middle income countries (LMICs), where more than 80% of service-users are living [10], there is less prioritization and government support for either mental health care provision or involvement of service users [10,11]. In many of these countries, there are no policies and laws to direct mental health programs and/ or the policies and laws are not aligned with human rights recommendations (e.g., social care, participation) or are poorly implemented [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In low-and-middle income countries (LMICs), where more than 80% of service-users are living [10], there is less prioritization and government support for either mental health care provision or involvement of service users [10,11]. In many of these countries, there are no policies and laws to direct mental health programs and/ or the policies and laws are not aligned with human rights recommendations (e.g., social care, participation) or are poorly implemented [10,11]. Service-users are exposed to stigma and discrimination [12,13] and have several unmet needs [13], exemplified by suffering of illness and disability [14], impoverishment [15], premature mortality [16,17], and human rights abuses(e.g., being chained or kept in isolation) [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…This high occurrence is influenced by less prioritization for mental health services and insufficiency of mental health interventions [4]. It was found that more than 70% of the global mental health burden occurs in LMICs [5]. The American Psychological Association (APA) developed guidelines that play a crucial role in preventing mental health disorders by promoting a preventive perspective in psychological well-being (PWB).…”
Section: Introductionmentioning
confidence: 99%